Airports, cities and regions. - (:unkn) unknown (Routledge, 2014)
Since the emergence of urban systems, cities have developed in a mutually inter-dependent process of socio-economic dynamics and transportation linkages. In recent years, Airports worldwide have stepped beyond the stage of being pure infrastructure facilities while the complex dynamics that are taking place at and around international airports represent a crucial element in the post-industrial reorganisation of urban and regional systems. Airports are increasingly recognized as general urban activity centres; that is, key assets for cities and regions as economic generators and catalysts of investment in addition to being critical components of efficient city infrastructure. This book brings together contributions from renowned academic scholars and world leading practitioners to discuss insights gained from theory and practice. The first collection of papers reflects upon the general role and future of airports as well as their specific contribution to competitive advantages within a fast changing business and economic landscape. The second group of contributions ask about the role airports play within the innovation process that is inherently centred on generating and sharing knowledge. The third section of papers investigates the drivers of real estate developments on airport land and in the close vicinity of airports.
Keywords: Standort; Flughafen; Flughafenplanung; Stadtregion; Beschäftigung; Standortfaktor; Regionalwirtschaft; Großflughafen; Räumliche Verteilung; Cluster; Logistik; Unternehmensstandort; Wissensökonomie; Internationaler Vergleich; Flughafenunternehmen